Sensitivity Indicators Analysis and Regional Sustainable Development Status in Indonesia - Bakri, Bachril; Rustiadi, Ernan; Fauzi, Akhmad; Adiwibowo, Soeryo (Research and Development Agency Ministry of Home Affairs, 2017)
Indonesia is one of the largest archipelagic country in the world, with an area of 1,913,578.67 km2, and consists of 34 provinces, 415 regencies, and 93 cities. Since the end of centralistic governance under Soeharto's administration in 1999, Indonesia has adopted a decentralized governance system to deliver national and regional development. It has been noted that Indonesia has variations in social, economic, ecological, and institutional dimensions between a province to another province in Indonesia. This study aims to analyze the sensitivity of indicator and hierarchy of sustainability of province in Indonesia, using a scalogram method, and analyze the status of sustainable development of the regions, using cluster and flag analysis method. The research shows two most sensitive indicators, the ratio of paved road length to area width and the GDP per capita. Both of these indicators are very effective in increasing the sustainability of provincial development in Indonesia. Of the 33 provinces studied, 24 are at a moderate level of sustainability. Flag analysis showed that the SDG scenario is better than the NC-MEA and the BAU at Region I to III.